Grazing by semi‐feral cattle and horses supports plant species richness and uniqueness in grasslands. Issue 1 (21st March 2023) - Bonavent, Christoffer; Olsen, Kent; Ejrnæs, Rasmus; Fløjgaard, Camilla; Hansen, Morten D. D.; Normand, Signe; Svenning, Jens‐Christian; Bruun, Hans Henrik
Abstract: Question: How does naturalistic grazing (trophic rewilding with large herbivores), in contrast to mowing and free succession (no grazing), affect plant community composition and species richness in temperate grassland grazed by semi‐feral cattle and horses? Location: Mols Laboratory, Denmark. Methods: We investigated grazing exclosures in the rewilding area of the Mols Laboratory, four years after its establishment. We focused on moist to dry grassland vegetation, that is, excluding scrub and woodland. Each experimental block consisted of five 5 × 9 m plots, representing four fenced treatments, that is, summer‐only grazing, winter‐only grazing, full exclosure with annual autumn mowing and full exclosure with passive succession. The matrix (the fifth treatment) was grazed by large herbivores at close‐to‐natural densities, that is, regulated bottom‐up by the carrying capacity of the area. Hence, even the seasonal grazing treatments were grazed at close‐to‐natural animal density. Quantitative plant community composition was assessed using the point‐intercept method in 25 × 25 cm quadrats, supplemented with biomass calibration models based on additional quadrats, in which above‐ground plant biomass was harvested after recording and the material sorted to species and weighed. Uniqueness was assessed as the sum of inverse range sizes for constituent species (unicity). Results: We found an appreciably higher plant species richness in grazing treatments than under both annual mowing and full exclosure, but only minor differences between seasonal grazing treatments. Uniqueness was highest in year‐round and winter‐only grazing and lowest in summer‐only grazing. The forb:graminoid ratio tended to be high in the winter‐only grazing treatment, whereas annual mowing was associated with dominance of graminoids over forbs. Full‐exclosure plots had accumulation of litter and the lowest species richness. Initial heterogeneity between plots within blocks and a systematic difference between blocks in moist and dry grasslands may have diluted treatment effects at this early point after the onset of the experiment. Data analysis using the biomass estimates derived from the calibration models yielded only minor differences in the patterns described above, when compared to the results obtained using the raw number of intercepts. Conclusions: Naturalistic grazing is a goal in itself in ecological restoration, but also proposed as an efficient management tool to promote conservation of grassland plants and communities. We found both plant species richness and the prevalence of regionally rarer species (uni) to be higher with grazing than mowing or abandonment. Similarly, the tendency for forbs to prevail under grazing may translate into enhanced floral resources for anthophilous insects. Summer‐only grazing at low density of large herbivores was not significantly different from winter‐only and year‐round grazing, but this treatment was much closer to natural grazing than intensive summer grazing typical of agri‐environmental practices. Abstract : Grazing is a natural ecosystem process and, thus, restoring naturalistic grazing using feral animals may be seen as a restoration goal in itself, notwithstanding the effects on biodiversity. Nevertheless, the present study demonstrates that naturalistic grazing as a management tool may indeed create habitat for regionally uncommon species of conservation concern and probably enhance resource availability to flower‐seeking insects.